Independent German Learning Through the Mobile Learning Funeasylearn Application for the 10th Graders of Lintas Minat SMAN 9 Malang - Nadia Safira Salsabillah; Lilis Afifah (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2021)
This article aims to describe the independent learning process through FunEasyLearn application and student responses to the use of  application. The research method in this study was descriptive qualitative. Sources of data were 36 students of  10th grade IPS 2 SMAN 9 Malang, while data were obtained through two different techniques, namely observations and interviews. The results showed that the independent learning process through the FunEasyLearn application went well. This also helps students to build their independent learning skills. During the learning process, students were responsible for completing the exercises in the apps independently. Furthermore, they had no difficulty in operating the apps. They were also interested and motivated to learn German with the help of FunEasyLearn because it has colorful and illustrated features as well and various exercises so that easier for them to understand the material. Overall, students showed positive responses to the use of the apps independently. They stated that their vocabs mastery increased after using the apps. Therefore, the FunEasyLearn apps can be used continuously as an alterative media for students to enlarge German vocabulary and build their independent learning both in and outside of the classroom.